Analysis of Factors Influencing Cadre Performance in Providing Health Services at Posyandu for Mothers and Toddlers - Kartika Endarwaty Jusuf; Widy Susanty Abdulkadir; Sri Manovita Pateda (GLOBAL HEALTH SCIENCE GROUP, 2026)
Posyandu serves as a crucial frontline service for maternal and child health. Although child growth monitoring and nutrition recording in Gorontalo Province have reached 100% coverage, the quality of Posyandu cadre performance still varies. Understanding the factors that influence cadre performance is essential for improving service quality, especially among cadres without health-related educational backgrounds. This study aimed to analyze the factors associated with cadre performance in providing maternal and child health services at Posyandu. This study employed an observational analytic design with a cross-sectional approach. A total of 100 Posyandu cadres each with a non-health educational background were included using a total sampling technique. Data were collected using structured questionnaires that had undergone validity and reliability testing prior to use. The analysis examined the influence of training, motivation, health center support, and community involvement on cadre performance. The findings showed that training had a significant effect on cadre performance (p = 0.029; R² = 0.048), as did motivation (p = 0.009; R² = 0.068). Health center support was not significantly associated with performance (p = 0.814; R² = 0.001). Community involvement was identified as the most influential factor (p = 0.006; R² = 0.075). Cadre performance at Posyandu is strongly influenced by motivation and community involvement, while training remains essential for enhancing the competence of cadres with non-health educational backgrounds. Strengthening these key factors can help improve the quality of maternal and child health services at the community level.